2019
DOI: 10.31820/pt.28.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Fluency and Feeling of Rightness

Abstract: Feeling of Rightness (FOR) is a metacognitive experience accompanying people's intuitive answers that predicts the probability of subsequently changing answers (Thompson, Prowse Turner, & Pennycook, 2011). Previous research suggested FOR judgments are influenced by cues such as fluency, i.e., the ease with which an answer comes to mind. In the current paper, we examine the relationship between FOR, fluency, and answer changes; in particular, we were interested in whether answer fluency drives the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…This finding is in line with previous research on Feelings of Rightness (i.e. subjective confidence in an initial judgement) and resistance to changing one's mind (Thompson et al, 2013;Wang & Thompson, 2019). Previous research has also shown that confident initial judgments and first impressions are less likely to change in individual as well as in group decision-making (Kruglanski et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in line with previous research on Feelings of Rightness (i.e. subjective confidence in an initial judgement) and resistance to changing one's mind (Thompson et al, 2013;Wang & Thompson, 2019). Previous research has also shown that confident initial judgments and first impressions are less likely to change in individual as well as in group decision-making (Kruglanski et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has also shown that confident initial judgments and first impressions are less likely to change in individual as well as in group decision-making (Kruglanski et al, 1993). Similar results have been found in a range of judgments, including consumer choices (Folke et al, 2017), syllogistic reasoning tasks (Shynkaruk & Thompson, 2006;Thompson et al, 2011Thompson et al, , 2013Wang & Thompson, 2019), medical diagnoses and treatment decisions (Dreiseitl & Binder, 2005;Jaimes et al, 2013;Krupat et al, 2017;Pandharipande et al, 2016), and moral dilemmas (Vega et al, 2020). The phenomenon is therefore not limited to lay people, but it is also applicable to experienced professionals.…”
Section: Discussionsupporting
confidence: 62%
“…Instead, it is possible that faster processed sequences were judged as more familiar simply because they were more easily processed. This is because fluency is known to evoke a “feeling of rightness,” which can bias judgments (e.g., Thompson, Evans, & Campbell, 2016; Topolinski, 2012; Wang & Thompson, 2019). Accordingly, it is possible that ease of processing may mediate the association between familiarity judgments and response times.…”
Section: Discussionmentioning
confidence: 99%